Zero-field steps and coherent emission of externally heated long Josephson junctions. (9th November 2016) - Grib, Alexander; Seidel, Paul; Tonouchi, Masayoshi
Abstract: IV -characteristics of stacks of two inductively interacting long Josephson junctions with the homogeneous and inhomogeneous distributions of critical currents were investigated numerically. It was assumed that the inhomogeneous linear distribution of critical currents along the junction was created by heating of one end of the stack. Even zero-field steps were found in the IV -curve of the stack with the homogeneous distribution of critical currents, whereas odd zero-field steps appeared in the IV -curve of the stack with the heated end. Due to the inductive interaction between junctions in a stack of two junctions, each of the zero-field steps splits into two steps which correspond to frequencies of collective excitations in the system. Strong coherent emission was found at the step which corresponds to the frequency of in-phase oscillations.